Calebin A targets the HIF-1α/NF-κB pathway to suppress colorectal cancer cell migration - Brockmueller, Aranka; Girisa, Sosmitha; Motallebi, Mahzad; Kunnumakkara, Ajaikumar B.; Shakibaei, Mehdi (Frontiers in Pharmacology, 2023)
Background: Hypoxia-inducible factor-1α (HIF-1α) is one of the major tumorassociated transcription factors modulating numerous tumor properties such as tumor cell metabolism, survival, proliferation, angiogenesis and metastasis. Calebin A (CA), a compound derived from turmeric, is known for its anti-cancer activity through modulation of the NF-B pathway. However, its impact on HIF-1α in colorectal cancer (CRC) cell migration is unknown.Methods: Human CRC cells (HCT-116) in 3D-alginate and monolayer multicellular-TME (fibroblasts/T-lymphocytes) were subjected to CA or HIF-1α inhibitor to explore the efficacy of CA on TME-induced inflammation, migration, and tumor malignancy.Results: CA significantly inhibited TME-promoted proliferation and migration of HCT-116 cells, similar to HIF-1α inhibitor. Colony formation, toluidine blue staining, and immunolabeling showed that CA inhibited the migration of HCT-116 cells partly by inhibiting HIF-1α, which is critical for CRC cell viability and these observations were confirmed by electron microscopy. In addition, Western blot analysis confirmed that CA inhibited TME-initiated expression of HIF-1α, biomarkers of metastatic factors (such as NF-B, β1-integrin and VEGF) and promoted apoptosis (caspase-3), in a manner comparable to HIF-1α inhibitor. Finally, TME induced a purposeful pairing between HIF-1α and NF-B, suggesting that synergistic interplay between the two tumor-associated transcription factors is essential for CRC cell malignancy and migration and that CA silences these factors in tandem.These results shed light on a novel regulatory modulation of CA signaling in CRC cell migration, partially via HIF-1α/NF-B with potentially relevant implications for cancer therapy.